Standardization of Selected Asavas and Arishtas - K. Santosh, M.; Shaila, D.; Sanjeeva Rao, I. (Asian Journal of Chemistry, 2010)
In the present investigation and standardization of selected asavas and arishtas have been done by preliminary phytochemical, chromatographic and analytical studies. The preliminary phytochemical study revealed the presence of phenolic compounds in all the selected asavas and arishtas and no flavanoids have been detected. Out of the nine solvent systems used for the chromatographic study, only the solvent n-butanol : glacial acetic acid: water system showed a good separation of asavas and arishtas and in other solvent systems streaking was observed. Aravindasava,asokarista, dasamularista and kumaryasava gave positive results for Borntrager reaction. Analytical study revealed the lowest pH . 3.42 in kumaryasava and highest pH 4.8 in amritarista; specific gravity ranges in betwecn 1.0177 (aravindasava) and 1.2612 (dasamularista) and lowest alcohol content was observed in amritarista (3.6%) and highest in asokarista (10.5%).